Tracing future spring and summer drying in southern Africa to tropical lows and the Congo Air Boundary - Howard, Emma; Washington, Richard (My University, 2020)
In southern Africa, models from phase 5 of the Coupled Model Intercomparison Project (CMIP5) predict robust future drying associated with a delayed rainy-season onset in the austral spring and a range of wetting and drying patterns in the austral summer. This paper relates these rainfall changes to dynamical shifts in two classes of weather systems: the Congo Air Boundary (CAB) and tropical lows. Objective algorithms are used to track these features in CMIP5 model output. It is then established that the climatological locations and frequencies of these systems are reasonably well represented in the CMIP5 models. RCP8.5 end-of-twenty-first-century projections are compared with historical end-of-twentieth-century simulations. Future projections in tropical-low locations and frequencies diverge, but indicate an overall average decrease of 15% and in some cases a northward shift. The projected spatial change in the tropical-low frequency distribution is weakly positively correlated to the projected spatial change in the austral summer rainfall distribution. Meanwhile, future projections indicate a 13% increase in CAB frequency from October to December. This is associated with the gradual climatological CAB breakdown occurring half a month later on average in end-of-twenty-first-century RCP8.5 projections. A delay in the gradual seasonal decline of the CAB prevents rainfall to the south of the CAB’s mean position, most of which is shown to occur on CAB breakdown days, hence creating the austral spring drying signal and delayed wet-season onset. Intermodel variability in the magnitude of CAB frequency increase is able to explain intermodel variability in the projected drying.
Keywords: Climate Change; CMIP5; Congo Air Boundary; Southern Africa; Tropical Lows; UMFULA